Diagnosis And Clinical Course of Chronic Generalised Periodontitis in Connective Tissue Dysplasia (Eurasian Medical Research Periodical, 2022)
This article discusses the analysis of the influence of behavioral factors and self-control of type 2 diabetes mellitus on the development of purulent-necrotic process of the lower extremities.